PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEMAMPUAN MANAJERIAL, KARAKTERISTIK PEKERJAAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DINAS PEMUDA, OLAHRAGA, PARIWISATA DAN KEBUDAYAAN KABUPATEN BARITO SELATAN DI BUNTOK - Sri Demidiyeti (JURNAL KINDAI, 2021)
Abstract : The purpose of this research was to analized the Effects of Transformational Leadership, Managerial Ability, Job Characteristics, Work Motivation of employee of Sports, Youth, Tourism and Culture Office in Buntok, South Barito Regency. The objects of the study are the employee of the office as many as 67 people. Based on type of research, the writer in conducting the research uses saturation sampling. Data collection techniques using Questioners, Interview and Study Literature Method. Analysis of the data used Multiple Regression Analysis Test. The result showed : (1) Work Motivation has a dominant influence on Performance of employee of Sports, Youth, Tourism and Culture Office in Buntok, South Barito Regency has proved by the beta coefficient 0,392 most higher value than other variables. (2) Simultaneously Transformational Leadership (X1), Managerial Ability (X2), Job Characteristics (X3), Work Motivation (X4) have a significant effect on the Performance of employee of Sports, Youth, Tourism and Culture Office in Buntok, South Barito Regency.(3) Partially Transformational Leadership (X1), Managerial Ability (X2), Job Characteristics (X3), Work Motivation (X4) have a significant effect on the Performance of employee of Sports, Youth, Tourism and Culture Office in Buntok, South Barito Regency. Keywords : Transformational Leadership, Managerial Ability, Job Characteristics, Work Motivation, performance